Impact of cardiometabolic index on long-term mortality in young adults with type 2 diabetes mellitus - Aihua Li; Ziying Zhou; Xiaoli Chen; Yubo Liu; Qilin Ma (PLoS ONE, 2026)
Background The cardiometabolic index (CMI) has been utilized in recent years to detect patients with type 2 diabetes mellitus (T2DM). Given the consistent annual rise in the incidence of T2DM among young adults, the relationship between CMI and mortality risk among those with early-onset T2DM remains to be determined. Methods We enrolled 2,188 participants aged 20–65 with diabetes from the National Health and Nutrition Examination Survey (NHANES) 1999–2018. Weighted Cox proportional hazard regression models were employed to evaluate hazard ratios (HRs) with 95% confidence intervals (CIs). Restricted cubic spline (RCS) curves were utilized to assess linear associations. Stratified and interaction analyses were performed. Results We find that higher CMI is strongly associated with an increased risk of all-cause mortality ( p = 0.005) and cardiovascular mortality ( p = 0.020) in the strictest model. RCS analysis revealed a linear relationship between CMI and mortality. Subgroup and interaction analysis showed no statistical significance. Conclusions The higher CMI level is correlated with all-cause and cardiovascular mortality risk among young individuals with diabetes mellitus, and serves as a comprehensive and effective prognostic indicator for long-term health.